Steroid Induced Cushing’s Syndrome in an Asthmatic patient: a Case Report - Sumol RATNA; Sachet DAWAR; V.D. VERMA; Yogendra BHATI; Divyesh SRIVASTAVA; Ankit OM; Jenya SAXENA (Modern Medicine)
Glucocorticoid therapies are used widely in arrange of medical conditions including respiratory, allergic, inflammatory and autoimmune diseases. All forms of glucocorticoid delivery, even at therapeutic doses, have the potential to cause Cushing’s syndrome. Here, we present a case of exogenous Cushing’s syndrome resulting from recurrent use of intermittent high dose oral prednisone to treat asthma exacerbation.